Tantangan Implementasi ASEAN Community: Kasus di Kota Malang - Rijal, Najamuddin Khairur (Insignia: Journal of International Relations, 2017)
Abstract This paper examines the challenges of implementing the ASEAN Community that are elaborated based on the understanding and views of the management of International Relations Students Association in Malang. The data used is the primary data obtained from the results of structured interviews and questionnaires to 60 respondents. While secondary data is used to support the discussion. As the result, there are three challenges of implementing the ASEAN Community. First, the understanding of society related to the description of the characteristics/goals of each pillars of ASEAN Community is low. The second challenge is people are more familiar with the term of MEA, so there are reduction of understanding about ASEAN Community is limited to the economic dimension. Third, the lack of understanding and the reduction of understanding is inseparable from the source of information about ASEAN Community which originated more dominant from secondary information. Keywords: ASEAN Community, AEC, Malang City Abstrak Tulisan ini mengkaji mengenai tantangan implementasi ASEAN Community yang dielaborasi berdasarkan pengetahuan dan pandangan mahasiswa pengurus Himahi di Kota Malang. Data yang digunakan merupakan data primer yang diperoleh dari hasil wawancara terstruktur dan pengisian angket kepada 60 responden. Adapun data sekunder digunakan untuk mendukung uraian pembahasan. Hasil penelitian menemukan bahwa ada tiga tantangan dalam implementasi ASEAN Community. Pertama, pemahaman masyarakat masih rendah terutama berkaitan dengan penjabaran dari karakteristik/tujuan masing-masing pilar ASEAN Community. Tantangan kedua adalah masyarakat lebih familiar dengan istilah MEA sehingga terjadi reduksi pemahaman tentang ASEAN Community hanya sebatas pada dimensi ekonomi. Ketiga, rendahnya pemahaman dan adanya reduksi pemahaman itu tidak terlepas dari sumber informasi tentang ASEAN Community yang lebih dominan diperoleh dari informasi sekunder. Kata-kata Kunci: ASEAN Community, MEA, Kota Malang